La tour d’ivoire : aventures et mésaventures de l’autonomie du littéraire - Paolo Tamassia (Revue Italienne d'Etudes Françaises)
French literary history is characterised by an alternation of two opposing positions: on the one hand, literature has sought legitimacy by relying on other cultural practices (philosophy, politics, science, religion) while, on the other hand, she has tended to assert herself in total autonomy. From the Romantic period onwards, this alternation became more complex, as the two positions confront each other in a tight dialectic to the point where they succeeded one another or coexisted in the reflection and in the literary practice of the same author, and this confrontation continues into the twentieth and twenty-first centuries. We need to consider the different issues at stake in the choice or rejection of the autonomy of the literary.